New record of Artibeus aequatorialis Andersen, 1906 (Chiroptera: Phyllostomidae) for northwestern Colombia - Palacios-Mosquera, Leison; Copete-Mosquera, Yucely del Carmen; Jimémez-Ortega, Alex Mauricio; Mantilla-Meluk, Hugo; Velazco, Paúl M. (THERYA, 2018)
The Neotropical fruit bats of the genus Artibeus are distributed from southern México to northern Argentina occupying a wide array of different habitats. Of the 14 species present in Colombia, 85.7 % (n = 12) occur in the department of Choco. Bat inventories were carried out by the Consejo Comunitario Mayor de Istmina and Medio San Juan (COCOMINSA) and the Universidad Tecnológica del Chocó in the corregimiento de Chiqui Choqui, municipality of Medio San Juan. We present a new record of A. aequatorialis for Colombia, that makes an important addition to the bat fauna of Chocoan biogeographic region and is the northernmost record of the species. Our specimen of A. aequatorialis was collected in the Chiqui Choqui locality, that belongs to the district of Alto-Atrato San Juan that is a poorly study area, whose diversity is threatened by human activities, like deforestation and mining activities.